(untitled) (The Conference Hub, 2025)
This article analyzes the economic and organizational and legal essence of investment and construction processes, their structural stages, participants, and modern approaches to their management on a scientific-theoretical and practical basis. The long-term nature, capital intensity, technological complexity, and high risks of construction projects indicate the need to form an effective management system in this area. The study highlights management systems based on international methodologies (PMBOK, PRINCE2, BIM), considers existing problems in Uzbekistan, and measures to eliminate them. The article also substantiates the economic efficiency of investment projects, functional relationships between stakeholders, and the advantages of digitalization principles.